Spillover Effects of Budgetary Policies in Monetary union: The Case of West African Economic and Monetary Union - Kane, Chérif Sidy (International Journal of Economics and Financial Issues, 2018)
With the help of a vector model for dynamic panel vector error correction, this article examines the extent to which a country’s policy shocks spread to the economic activity of other countries in the West African Economic and Monetary Union. The results of one part, the emergence of externalities that cause asymmetric shocks and another part, the public expenditure shocks induce greater spillover effects on economic growth than public revenue shocks. Both results imply the structural heterogeneity of economies, leading to an uneven distribution of the benefits and costs of a common monetary policy. Therefore, corrective measures can be applied, through a real policy mix that can reduce the risks of instability related to budgetary externalities. Keywords: Budgetary Externality, Structural Heterogeneity, Panel Vector Error Correction Model, West African Economic and Monetary Union JEL Classifications: F14, F15, F41 DOI: https://doi.org/10.32479/ijefi.7435